GELANGGANG REMAJA DI MUARA TEWEH (MUARA TEWEH YOUTH CENTERS) - Nursyifa, Findara Illa; Anhar, Pakhri (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
The importance of non-academic education for teenagers is considered no less important in order to the development of various potentials within them. Teenagers in Muara Teweh were considered quite enthusiastic for participating in various types of activities. However, there are some that are known to be frequent obstacles, including the unavailability of place and facilities, and environments that tend to be determinative. This situation is feared will reduce the interest of teenagers in exploring their potential interests and talents more freely. This is the background of the need to procure a place in the form of a youth center that has a function for accommodating these development activities but also offers a fun atmosphere, dynamic and flexible, so that teens can comfortably carry out their activities. The method that is used is an architectural psychology approach by observing the characteristics of teenagers as a design reference. This is manifested by the concept of a youth cultural space that is applied to architectural elements in both indoor and outdoor space.